Remineralizing effect of a fluoridated gel containing sodium hexametaphosphate: An in vitro study - Gonçalves, Francyenne Maira Castro [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP]; Nunes, Gabriel Pereira [UNESP]; Emerenciano, Nayara Gonçalves [UNESP]; Garcia, Luhana Santos Gonzales [UNESP]; Báez Quintero, Liliana Carolina [UNESP]; Neves, José Guilherme [UNESP]; Danelon, Marcelle [UNESP] (Elsevier, 2018)
Objectives: To evaluate in vitro the effect of neutral pH topical gels with reduced fluoride concentration (F), supplemented or not with sodium hexametaphosphate (HMP) on the remineralization of dental enamel, using a pH-cycling model. Materials and methods Bovine enamel blocks with caries-like lesions were randomly treated with five gels (n = 24/group): without F/HMP (Placebo); 4500 ppm F (4500F), 4500F plus 9% HMP (4500F + HMP); 9000 ppm F (9000F); and 12,300 ppm F (Acid gel). After pH-cycling, the percentage of surface hardness recovery (%SHR), integrated loss of subsurface hardness (ΔKHN), and concentrations of loosely- (CaF2) and firmly-bound (FA) fluoride formed and retained in/on enamel were determined. The results were analyzed by ANOVA followed by the Student-Newman-Keuls test (p < 0.001). Results: The 4500F + HMP gel promoted the highest %SHR among all groups; the lowest ΔKHN was achieved by 4500F + HMP and Acid gel, without significant differences between these. The Acid gel group presented the highest CaF2 and FA formed and retained on/in enamel (p < 0.001). Conclusion: Based on the present results, the addition of 9% sodium hexametaphosphate to a gel with reduced fluoride concentration (4500F) was able to significantly enhance the remineralization of artificial carious lesions in vitro when compared to 4500F, reaching protective levels similar to an acidic formulation with ∼3-fold higher fluoride concentration.
Keywords: Dental enamel; Gel; Phosphates; Remineralization